Toy story of terror! [videorecording (DVD)]. (Disney/Pixar, 2014)
What starts out as an exciting road trip for the Toy Story gang takes an unexpected turn for the worse following a detour to a roadside motel. After Mr. Potato Head suddenly disappears, his friends find themselves caught up in a hilarious mystery that must be solved before they suffer the same fate in this thrilling story of TERROR!